2020
DOI: 10.1093/qjmed/hcaa052.022
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Spontaneous Urticaria and Gut Flora (Lactobacilli)

Abstract: Background and Aims Chronic Urticaria is a common disorder which is defined by recurrent occurrence of wheals and sometimes angioedema. It has a notable influence on the patient’s quality of life. Regulation of the immune system is one of the important roles of the gut microbiota. Objective Comparing the frequency and bacterial load of Lactobacillus between patients with chronic urticaria and healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 36 Namely, the relative abundance of Lactobacillus was significantly higher in fecal samples from healthy controls than in those from patients with chronic urticaria. 18 It has been revealed that probiotic bacteria could modulate the Th1/Th2 balance, suggesting that the development of inflammatory diseases, including allergies, could be prevented. 37 Researchers have reported the administration of Bifidobacterium and Lactobacillus as probiotics to alleviate inflammatory responses by ameliorating dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Namely, the relative abundance of Lactobacillus was significantly higher in fecal samples from healthy controls than in those from patients with chronic urticaria. 18 It has been revealed that probiotic bacteria could modulate the Th1/Th2 balance, suggesting that the development of inflammatory diseases, including allergies, could be prevented. 37 Researchers have reported the administration of Bifidobacterium and Lactobacillus as probiotics to alleviate inflammatory responses by ameliorating dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“… 17 For example, fecal samples from healthy controls had a significantly higher relative abundance of Lactobacillus than that from patients with chronic urticaria. 18 The microbial population decreased in the CSU group compared with the healthy control one. Patients with CSU exhibited increased beta diversity in the abundance of Enterobacteriaceae, whereas that of Bacteroides, Faecalibacterium, Bifidobacterium , and Ruminococcaceae was significantly reduced in patients with CSU.…”
Section: Introductionmentioning
confidence: 90%
“…However, about 50% of patients are resistant to second-generation nonsedating H1-antihistamines, and the precise pathogenesis remains largely unknown but seems to be associated with low-level systemic or intestinal inflammation (6).…”
mentioning
confidence: 99%
“…The hypothesis was to determine the probable association of intestinal microbiome with chronic spontaneous urticaria. The gut microbiota of patients with chronic spontaneous urticaria and healthy individuals were obtained by 16s rRNA massive sequencing.In this review, we discuss the different factors that can exacerbate established chronic spontaneous urticaria, prolong the duration of the condition and encourage the need for second and third line therapy.However, about 50% of patients are resistant to second-generation nonsedating H1-antihistamines, and the precise pathogenesis remains largely unknown but seems to be associated with low-level systemic or intestinal inflammation(6).The gastrointestinal microbiota provides a vast and continuous stimulation for the immune system. Chronic spontaneous urticaria seems to be associated with low-level systemic or intestinal inflammation(7,8).Intestinal permeability was reported to be increased in chronic spontaneous urticaria and this was partly reversed by 24 days on a reduced pseudoallergen diet.Increasing evidence suggests that the gut microbiome plays a role in the pathogenesis of allergy and autoimmunity(9).…”
mentioning
confidence: 99%